Analisis kesulitan mahasiswa pendidikan geografi dalam memahami materi ajar SMA berbasis kurikulum merdeka di kampus UNADA Banda Aceh - Kartika, Devya; Wahyuni, Intan; Artina, Artina (Nur Science Institute, 2025)
Teaching difficulties are a big obstacle for teachers, especially in managing the student learning environment. These barriers can be psychological, sociological, or physiological. The Independent Curriculum emphasizes student independence and requires adjustments to technology and infrastructure. Observations show that FKIP UNADA Banda Aceh students have not mastered the teaching materials based on the Independent Curriculum. This study analyzes these difficulties and aims to determine the difficulties of geography education students in understanding the high school teaching materials based on the Independent Curriculum at FKIP UNADA Banda Aceh. This study uses a qualitative descriptive method. The study results showed that 77.1% of Geography Education students had a